المجلس القيادي الرئاسي اليمني (النشوء والاستمرار) - عبدالرحمن أحمد; عبدالرزاق عماد صلاح (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The Yemeni Presidential Leadership Council was announced on April 7, 2022, with President Abd-Rabbu Mansour Hadi transferring power to the eight-member council. The council’s tasks include managing the state politically and security-wise during the transitional period, adopting a balanced foreign policy, and enhancing security and counter-terrorism efforts. The council has been granted extensive powers, including appointing governors, judges, and security directors, ratifying agreements, and establishing diplomatic missions. The council faces significant challenges that require wisdom in handling the complex situations in Yemen, including tensions among various armed factions.